Hubungan Lingkar Skrotum dengan Kualitas Semen Sapi Kuantan Riau - Jiyanto Jiyanto; Pajri Anwar (Politeknik Negeri Jember, 2019)
The aim of this study was to determine the correlation between scrotal circumference and semen quality of the Riau Kuantan cattle. The study was conducted in Benai District, Kuantan Singingi Regency. The material used was 15 Kuantan bulls. The parameters observed were scrotal circumference, semen quality and the correlation between scrotal circumference and semen quality. The results of this study indicated that the size of Kuantan cattle scrotum circumference was 23.06 cm; viability 76.67%; and motility 58%. The results of regression analysis which conducted on scrotal circumference for the viability and motility showed not significant (P>0.05). The correlation between scrotal circumference with spermatozoa viability of Kuantan cattle showed a moderate correlation of 0.40. The relationship between scrotal circumference with spermatozoa motility in Kuantan cattle showed a low correlation of 0.22. The regression equation obtained to determine the relationship between scrotal circumference with viability and motility of spermatozoa were Y = 45.44 + 1.35X and Y = 44.77 + 0.57X, respectively. The results of this study indicated that scrotal circumference cannot be made as determinant of spermatozoa quality of in Riau Kuantan bulls.